2023
DOI: 10.1186/s11689-023-09477-x
|View full text |Cite
|
Sign up to set email alerts
|

No difference in extra-axial cerebrospinal fluid volumes across neurodevelopmental and psychiatric conditions in later childhood and adolescence

Abstract: Background While autism spectrum disorder has been associated with various organizational and developmental aberrations in the brain, an increase in extra-axial cerebrospinal fluid volume has recently garnered attention. A series of studies indicate that an increased volume between the ages of 6 months and 4 years was both predictive of the autism diagnosis and symptom severity regardless of genetic risk for the condition. However, there remains a minimal understanding regarding the specificity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 75 publications
0
3
0
Order By: Relevance
“…2). Indeed, two large studies have recently reported that EA-CSF volumes of ASD children above the age of four do not differ significantly from those of controls 19,20 . Taken together, these findings suggest that excessive EA-CSF volumes and EA-CSF/TBV ratios in the sub-group described above are a transient characteristic that appears during early development and disappears later in childhood as the children mature.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…2). Indeed, two large studies have recently reported that EA-CSF volumes of ASD children above the age of four do not differ significantly from those of controls 19,20 . Taken together, these findings suggest that excessive EA-CSF volumes and EA-CSF/TBV ratios in the sub-group described above are a transient characteristic that appears during early development and disappears later in childhood as the children mature.…”
Section: Discussionmentioning
confidence: 99%
“…It was suggested that this increased EA-CSF/TBV ratio may indicate a unique etiology of ASD. Two large follow-up studies examining older ASD children did not find any differences in EA-CSF volumes in ASD children 4-years-old and older 19,20 , suggesting that EA-CSF differences are transient and normalize during later childhood.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation